Applying the Precautionary Principle to Private Persons : Should it Affect Civil and Criminal Liability? - Pardy, Bruce (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2002)
The precautionary principle, developed in international environmental law, is a prospective concept. It can be used to decide what should be allowed to occur in the future. The question addressed in this article is whether, in domestic law, the precautionary principle should be applied retrospectively. Should precautionary behaviour be used as a standard to apply to the past actions of private persons, so as to judge whether those persons have acted legally ? In the civil realm, the answer is « yes ». Applying the precautionary principle in civil cases removes foreseeability requirements, and transforms liability based on fault into strict liability. In the criminal sphere, retrospective application of the precautionary principle is not appropriate. To require precautionary action on the part of an accused in an environmental prosecution transforms strict liability into absolute liability, and creates the potential for criminal punishment in the absence of culpability.